Clear Cell Sarcoma of Kidney in a Neonate - Avinash Sukdev Jadhav; Sanjay Jain; Neeraj Tuteja; Leeladhar Agrawal (EL-Med-Pub, 2014)
A rare case of clear cell sarcoma of kidney (CCSK) especially in a neonate presented as abdominal mass in left flank. He was hospitalized, investigated and operated upon. Histopathology confirmed the diagnosis of clear cell sarcoma of the kidney. Post-operatively, chemotherapy was given according to the NWTS-5 protocol. During follow-u, the patient has shown good recovery after 7 months of surgery.